PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRUE OR FALSE STATEMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 26 PADANG - Novita Sari, Resi; Mukhni, Mukhni; Pratiwi, Merina (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was carried out due to the studentsâ low understanding of mathematical concept in class VIII of SMPN 2 Padang. This research was intended to reveal the development of the studentsâ understanding of mathematical concept by using True Or False Statement active learning strategy an to seeÂ whether the mathematical conceptual understanding of the student taugh by using True Or False Statement active learning strategy was better than that of student taught by using conventional learning in class VIII of SMPN 26 Padang. The instrument of the research were a quiz and a posttest. The data gotten was analyzed by usingÂ Â Â t-test assisted with software MINITAB. Based on the result of dat a analysis, it was figured out that p-value was smaller than a indicating that the mathematical conceptual understanding of the students taught by using True Or False Statement active learning strategy was better than that of students taught by using conventional learning.